The cephalic labial gland secretions of two socially parasitic bumblebees Bombus hyperboreus (Alpinobombus) and Bombus inexspectatus (Thoracobombus) question their inquiline strategy - Brasero N.; Martinet B.; Lecocq T.; Lhomme P.; Biella P.; Valterova I.; Urbanova K.; Cornalba M.; Hines H.; Rasmont P. (Insect Science, 2018)
Social parasitic Hymenopterans have evolved morphological, chemical, and behavioral adaptations to overcome the sophisticated recognition and defense systems of their social host to invade host nests and exploit their worker force. In bumblebees, social parasitism appeared in at least 3 subgenera independently: in the subgenus Psithyrus consisting entirely of parasitic species, in the subgenus Alpinobombus with Bombus hyperboreus, and in the subgenus Thoracobombus with B. inexspectatus. Cuckoo bumblebee males utilize species-specific cephalic labial gland secretions for mating purposes that can impact their inquiline strategy. We performed cephalic labial gland secretions in B. hyperboreus, B. inexspectatus and their hosts. Males of both parasitic species exhibited high species specific levels of cephalic gland secretions, including different main compounds. Our results showed no chemical mimicry in the cephalic gland secretions between inquilines and their host and we did not identify the repellent compounds already known in other cuckoo bumblebees.